2007
DOI: 10.5172/conu.2007.26.2.225
|View full text |Cite
|
Sign up to set email alerts
|

The negative attitudes of nurses towards older patients in the acute hospital setting: A qualitative descriptive study

Abstract: The analysis of data with nurses reveals two themes and subthemes. 'Marginalisation and oppression of the older person' shows the ways in which nurses perceive older people are relegated to a lower status in the acute care setting, how this is 'contagious' and how 'lack of time' for care for older people is problematic and has become their 'catchcry'.'Stereotyping the older person' depicts some of the ways in which this evolves, for example, through 'Chinese Whispers' (UsingEnglish.com 2006), but has become pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 2 publications
5
132
0
12
Order By: Relevance
“…Furthermore, Nolan and colleagues noted the continued existence of ageism, prejudice, and impoverished environments characterized by poor conditions, attitudes, and standards of care. Other reports have revealed similar findings (e.g., Cooper, Selwood, & Livingston, 2008;Hanson, 2014;Higgins, Der Riet, Slater, & Peek, 2007;Mullan, 2009), with further research pinpointing the negative impact of diminished resources on care for older people, highlighting the practical issues faced by nurses in these environments (Adibelli & Kılıç, 2013). Taken together, these reports suggest that working on wards where older people are cared for may be considered particularly difficult and challenging and be associated with low staff motivation and morale.…”
Section: Intervention Contextsupporting
confidence: 62%
“…Furthermore, Nolan and colleagues noted the continued existence of ageism, prejudice, and impoverished environments characterized by poor conditions, attitudes, and standards of care. Other reports have revealed similar findings (e.g., Cooper, Selwood, & Livingston, 2008;Hanson, 2014;Higgins, Der Riet, Slater, & Peek, 2007;Mullan, 2009), with further research pinpointing the negative impact of diminished resources on care for older people, highlighting the practical issues faced by nurses in these environments (Adibelli & Kılıç, 2013). Taken together, these reports suggest that working on wards where older people are cared for may be considered particularly difficult and challenging and be associated with low staff motivation and morale.…”
Section: Intervention Contextsupporting
confidence: 62%
“…[7,21] Given the opportunity to acquire knowledge about, gain experience with, and realize the importance of elder care, nursing students can replace negative attitudes with more objective (positive) views. The finding of a significant effect of the gerontology course on negative attitudes also supports the utility of the triadic theory of attitude [8] which states that objective knowledge and experience of the common phenomena of aging can change people's cognition and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…[7,20] This situation is similar to reports regarding nurses working in acute or long-term care settings, who develop negative attitudes toward older patients. [6,20,21] Unfortunately, one report showed that nearly half of nursing students never received specific information about aging as part of their education. [22] Although American academic institutions made a decadelong, nationwide effort to improve gerontology competency in nursing curricula, [22] research in attitudes towards aging and the effect of gerontology education was limited during that time.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been documented in nurses working in acute or long-term care settings, who also develop negative attitudes toward older patients. [19,21] A key challenge in nursing curricula is how to provide educational experiences that promote positive attitudes, rather than reinforce negative stereotypes.…”
Section: Introductionmentioning
confidence: 99%